Simulation analysis of prestressed tensioning whole processon direct constraint method - Kaimin Liu (Functional Materials, 2017)
The accuracy simulation of the prestressed tensioning effect is the foundation of prestressed bridge design, construction and reinforcement. Direct constraint method was used in the application of prestressed tensioning whole process simulation analysis on the background of prestressed testing experiment. Its aim was to achieve the real simulation of interaction between prestressed tendon and concrete in the tensioning whole process. Three-dimensional solid elements were adopted to simulate pre-stressed reinforcement unit and concrete unit. Bilinear Coulomb friction was adopted as the friction form between prestressed tendon and concrete. Direct constraint method that has the characteristics of good stability and fast convergence speed was used to calculate the effective stress of prestressed tendon at each tension stage. The loss of one-way stress was also calculated. The effective prestressed values by simulation on direct constraints method can be well with the measured values and the theoretical values on Code for Design of Highway Reinforced Concrete and Prestressed Concrete Bridges and Culverts. The method has theoretical basis on accurately simulating the actual stress in different stages of the prestressed tendon. It can be helpful for bridge design and reinforcement. Методом прямого ограничения проведено моделирование процесса предварительного натяжения на основании экспериментов по тестированию предварительного напряженных систем. В качестве модельного объекта рассмотрено взаимодействие между предварительно напряженой арматурой и бетоном. Для имитации армирующих блоков и блоков бетона был адаптирован трехмерный метод упругого твердого тела. В качестве модели, описывающей силы трения, возникающие между предварительно напряженной арматурой и бетоном, рассматривается модель кулоновского трения. Для вычисления эффективных напряжений армирующей матрицы на разных этапах натяжения был использован метод прямого ограничения, обладающий хорошей стабильностью и высокой скоростью сходимости. Показано, что значения эффективных преднапряжений, полученные путем моделирования методом прямого ограничения, находятся в качественном согласии с экспериментальными и теоретическими значениями. Методом прямого обмеження проведено моделювання процесу попереднього натягнення на підставі експериментів по тестуванню попередньо напружених систем. В якості модельного об’єкту розглянуто взаємодію між переднапруженою арматурою і бетоном. Для імітації блоків, що армують та блоків бетону був адаптований тривимірний метод пружного твердого тіла. В якості моделі, яка описує сили тертя, що виникають між попередньо напруженою арматурою і бетоном, розглядається модель кулоновського тертя. Для обчислення ефективних напружень матриці, що армує, на різних етапах натягу був використаний метод прямого обмеження, що володіє гарною стабільністю та високою швидкістю збіжності. Показано, що значення ефективних переднапружень отриманих шляхом моделювання методом прямого обмеження, знаходяться в якісній згоді з експериментальними та теоретичними значеннями.